2003
DOI: 10.1046/j.1538-7836.2003.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective double-blind randomized study of the effects of four intravenous fluids on platelet function and hemostasis in elective hip surgery

Abstract: Summary.A prospective randomized double-blind study was performed to determine the effects of three colloids, Haemaccel, Gelofusine and albumin, and also saline on platelet activation, platelet aggregation (induced by adenosine diphosphate (ADP), epinephrine, collagen) platelet agglutination by ristocetin and other hemostatic variables in 55 patients undergoing primary unilateral total hip replacement. The¯uids were administered according to normal clinical practice and assessments were made immediately before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…A previous research letter has reported inhibition of ristocetin induced platelet aggregation by Haemaccel, 47 and in patients undergoing elective orthopaedic surgery, platelet aggregation seems to be inhibited by both Haemaccel and Gelofusine. 48 We do not yet know if the effects found are important in patients. It was particularly interesting that there was little change in the Sonoclot ACT (which measures the same aspects of coagulation as the conventional coagulation screen, the international normalised ratio and activated partial thromboplastin time), but there was a large change in TTP (which is not measured in the conventional coagulation screen).…”
Section: Discussionmentioning
confidence: 99%
“…A previous research letter has reported inhibition of ristocetin induced platelet aggregation by Haemaccel, 47 and in patients undergoing elective orthopaedic surgery, platelet aggregation seems to be inhibited by both Haemaccel and Gelofusine. 48 We do not yet know if the effects found are important in patients. It was particularly interesting that there was little change in the Sonoclot ACT (which measures the same aspects of coagulation as the conventional coagulation screen, the international normalised ratio and activated partial thromboplastin time), but there was a large change in TTP (which is not measured in the conventional coagulation screen).…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing hip replacement Evans et al. [6] found that platelet aggregation decreased similarly for albumin and two different gelatine solutions. In addition, aPTT increased and concentrations of coagulation factor VIII transiently decreased, but blood loss was comparable in all groups.…”
Section: Discussionmentioning
confidence: 99%
“…2. Three studies had a a low risk of bias in all domains [19][20][21], and five studies had a low risk in all domains except blinding [22][23][24][25][26]. (Table 1).…”
Section: Descriptivesmentioning
confidence: 99%